Essential fatty acids as major lipid fraction in Nostoc muscorum by optimization of mixotrophic culture - María Guadalupe Mata-Pérez; Diana Linda Cárdenas-Chávez; Roberto Rico Martínez; Juan Jáuregui-Rincón (Nova Scientia)
Linoleic and α-linolenic acids are essential fatty acids for animals and humans that must be provided in their diet. Several sources have been studied, however production by cyanobacterium Nostoc muscorum has not been thoroughly studied. We aim to evaluate the effect of mixotrophic culture on biomass and lipid content, and subsequently to characterize and quantify the fatty acids present in N. muscorum. The individual and interactive effects of three culture conditions (glycerol concentration, acetate concentration and culture time) on biomass and lipid production by N. muscorum were investigated through a three factor, three-level Box-Behnken experimental design of response surface methodology for process optimization. Glycerol and acetate addition proved to have a synergetic effect on growth of N. muscorum which caused an increased in biomass and lipid production at tenth day of culture compared to the control culture. Moreover, the fatty acid profile showed a high percentage of polyunsaturated fatty acids, especially linoleic (52.64%) and α-linolenic (33.34%), suggesting possible applications for nutraceutical and feed industries.